THE SENSE OF SAFETY AMONG CHILDREN AND TEENAGERS IN THE LIGHT OF EMPIRICAL RESEARCH - Grzegorzewska, Maria Katarzyna; Kapusta, Mariusz; Noga, Henryk; Migo, Piotr Pawel (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The social life is dominated by concepts such as aggression, violence, frustration. The symptoms of this phenomenon are present in schools, families and on the street. They may have different forms, from physical violence both verbal and mental. All this favours the crisis of values and authority. One of the main external causes are the mass media, that do create the lack of authority and values One of the conditions of a child healthy development is to provide him a sense of security, which at the end will be again emphasized, not only by the family but also by a school, carers, environment the police and organized prevention programs. The study shows how children and young people perceive the issues related to security.